2015
DOI: 10.3390/met5042413
|View full text |Cite
|
Sign up to set email alerts
|

Direct Aqueous Mineral Carbonation of Waste Slate Using Ammonium Salt Solutions

Abstract: Abstract:The carbonation of asbestos-containing waste slate using a direct aqueous mineral carbonation method was evaluated. Leaching and carbonation tests were conducted on asbestos-containing waste slate using ammonium salt (CH3COONH4, NH4NO3, and NH4HSO4) solutions at various concentrations. The CH3COONH4 solution had the highest Ca-leaching efficiency (17%-35%) and the NH4HSO4 solution had the highest Mg-leaching efficiency (7%-24%) at various solid dosages and solvent concentrations. The CaCO3 content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As-received red mud samples with residual water were dried at 105 • C in an oven for 48 h. The dried red mud was then mixed with solid NH 4 Cl (10:1 weight ratio, i.e., red mud sample with the addition of solid NH 4 Cl). A fixed weight ratio (10:1) was used in the present study because Jo et al [39] reported that the concentration of ammonium salt solutions had a slight effect on the alkaline earth metal leachability of waste material (i.e., waste slate). However, it should be noted that the weight ratio might affect the results of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…As-received red mud samples with residual water were dried at 105 • C in an oven for 48 h. The dried red mud was then mixed with solid NH 4 Cl (10:1 weight ratio, i.e., red mud sample with the addition of solid NH 4 Cl). A fixed weight ratio (10:1) was used in the present study because Jo et al [39] reported that the concentration of ammonium salt solutions had a slight effect on the alkaline earth metal leachability of waste material (i.e., waste slate). However, it should be noted that the weight ratio might affect the results of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Among inorganic solvents, an ammonium chloride (NH 4 Cl) solution has been reported as an appropriate solvent to leach alkaline earth metals from industrial by‐products such as steel slag, waste concrete and coal fly ash for aqueous mineral carbonation. This aqueous mineral carbonation has none or a small amount of a base solution such as NaOH solution for adjusting the pH, required during carbonation processes to induce calcium carbonate precipitation …”
Section: Introductionmentioning
confidence: 99%
“…This aqueous mineral carbonation has none or a small amount of a base solution such as NaOH solution for adjusting the pH, required during carbonation processes to induce calcium carbonate precipitation. 14 Microwave-assisted leaching in metallurgy has been investigated to reduce the processing time. 15 Microwave energy is nonionizing electromagnetic radiation with frequencies in the range of 300 MHz to 300 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the possibility of separating iron and sodium must necessarily be investigated to ensure that the restraining process can be conducted harmlessly. X-ray diffraction (XRD) [16] and scanning electron microscopy (SEM) coupled with energy-dispersive spectroscopy (EDS) [17] analysis are performed to determine the mineral phase of sodium in iron powder and tailing. The findings can aid in reducing R and in the subsequent sodium separation after direct reduction and may be beneficial in reducing the sodium carbonate consumption of current alumina production processes.…”
Section: Introductionmentioning
confidence: 99%